Effect of surface modification on silicon carbide particles with nanocrystalline spinel LZO for enhanced damping and mechanical property. (5th October 2015) - Singh, Subhash; Pal, Kaushik
Graphical abstract: Highlights: ZrO2 is coated on SiC particles through chemical precipitation and isothermal hydrolyzing route. Lithium zirconium oxide (LZO) is coated on SiC particles by isothermal hydrolyzing route. Surface morphology of SiC particles have been changed as reported in zeta potential measurements. Coating reduces interfacial reaction between reinforcements and matrix effectively. The resulting composite exhibits 90% higher stiffness and 3.8-fold increase in tensile strength. Abstract: In our proof-of-concept studies, pure aluminium matrix composites reinforced with spinel lithium zirconate (Li2 ZrO3, LZO) coated silicon carbide (SiC) particles were fabricated by stir casting. Initially, we presented the results of an investigation on spinel LZO coating layer on SiC particles of sub-micron size via facile isothermal hydrolyzing and chemical precipitation procedure under relatively low temperature. Composite materials combining high stiffness (storage modulus) and mechanical properties by reinforcing SiC@ZrO2 and SiC@LZO obtained by different techniques, thoroughly investigated by various characterization techniques. The amount and coverage of zirconia and LZO crystals on SiC surface were studied through X-ray energy dispersion spectroscopy (EDX) analysis and elemental mapping observation. Further, thermal conductivity and zeta potential characteristics of the surface modified SiC particles were investigated for adequate dispersion and stability of SiC particles. The resulting aluminium metal matrix composite exhibits 90% higher stiffness and 3.8-fold increase in tensile strength, respectively as compared to the pure aluminium.